CSF Officials Training Program 2006/2007 (Canadian Snowboard Federation, 2006)
The Canadian Snowboard Federation (CSF) Officials Training Program is meant to help all individuals who volunteer time and expertise to snowboarding events and competitions in Canada. The purpose of the Officials Training Program is to provide snowboard officials with a greater understanding of the role they will assume during a competition and to introduce them to the rules of snowboard competition, the International Rules of Competition (IRC) of the Fédération International de Ski (FIS). This introduction to officiating focuses on outdoor work (Venue setup, designation of officials, and the hands on running of the physical competition). There is a major component that is briefly touched upon, being the inside work (i.e. the tabulation, production of results and the coordination of all of the administrative aspects that are an integral part of the success of competition). OBJECTIVES: - To create a knowledgeable and qualified pool of snowboard officials who are needed at all levels of competition - from club to international levels - To create a pool of knowledgeable and experienced snowboard volunteers for the 2010 Olympics and Canada Winter Games - To improve the quality of Canadian snowboard competitions at all levels